Evaluation Of Theileria Parva Enolase As A Target For Designing New Generation Antiheilerial Drug - Icen-taşkın, İrmak; Munzuroğlu, Ömer (Bitlis Eren Üniversitesi, 2017)
Enolase (2-phospho-D-glycerate hydrolase) enzyme has been characterized extensively and approved as a molecular drug target for rational drug discovery in apicomplexans such as plasmodium sp., toxoplasma gondii  but not in the Theileria parva which causative agent of  East Coast Fever(ECF) engender serious economic losses.  For the aim of identifying a key drug target, we have analyzed Theileria parva’s enolase sequence and we have constructed three-dimensional (3D) structure of that enolase and mammalian host Bos taurus  enolase(BtEno). Constructed model was approved, structurally analyzed and conceivable ligand binding pockets were identified for the first time in the literature. In this study, we reported significant findings, a penta-peptide and three different dipeptide insertions in TpENO (D103W104G105Y106C107, T147D148, K261E262, K317L318), when compare the sequences of enolase gene with its counterpart host BtEno. The homology modeling revealed that these insertions constituted loops that absent in B. taurus enolase seem to be important lead structures which can be used as binding sites for inhibition of TpEno.